2018
DOI: 10.1111/sdi.12685
|View full text |Cite
|
Sign up to set email alerts
|

Do current quality measures truly reflect the quality of dialysis?

Abstract: The US End Stage Renal Disease (ESRD) Program, which came into existence in 1973, was initially envisioned to provide needed financial coverage for about 50 000 patients through Medicare. Over the past 45 years the evolution of the ESRD program has been quite different, and it now serves over one half million dialysis and transplant patients. The Medicare Improvements for Patients and Providers Act (MIPPA) of 2008 Section 153(c) requires the Centers for Medicare and Medicaid Services (CMS) to develop and imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The lowest PPPC subscores we observed in this pilot were for “finding common ground,” further suggesting this may be the primary communication barrier to patient-centered care in this population. Future studies in this population may be improved with engagement of geriatricians or geriatric interprofessional teams as an alternative to engagement of nephrologists, who have been trained in a disease-oriented approach to care, which is further reinforced by required quality reporting that does not prioritize patient-centeredness [1, 2, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest PPPC subscores we observed in this pilot were for “finding common ground,” further suggesting this may be the primary communication barrier to patient-centered care in this population. Future studies in this population may be improved with engagement of geriatricians or geriatric interprofessional teams as an alternative to engagement of nephrologists, who have been trained in a disease-oriented approach to care, which is further reinforced by required quality reporting that does not prioritize patient-centeredness [1, 2, 38].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Some in the dialysis community have questioned the value of including the dialysis adequacy and hypercalcemia measures in public reporting and the star ratings because they are already at high levels of achievement and not as meaningful as outcomes like mortality and hospitalization. 10,11,16,17 24 In contrast, one study reported that the Hospital Compare star ratings were associated with a better experience of care, lower risk-adjusted mortality, and lower readmission rates. 25 Clearly there is a fair amount of variability within and across star rating programs, something that has been reported across the Hospital, Nursing…”
Section: Ta B L Ementioning
confidence: 97%
“…Dialysis adequacy and hypercalcemia are generally considered to be both more directly attributed to, and actionable by, dialysis facilities. 10,11 It is possible that facilities' efforts to improve on these measures, combined with the star rating weighting scheme, had the unintended consequence of focusing provider efforts on intermediate outcomes, which can be improved over the shorter term but may ultimately be less important to patients than primary outcomes like mortality, hospitalizations, or vascular access. In hindsight, the DFC star ratings might have been more impactful on improving these primary outcomes if proportionally greater weight had been assigned to Domains 1 and 2.…”
Section: Ta B L Ementioning
confidence: 99%
“…Although metrics such as hemoglobin and Kt/V are simple to measure, it is becoming more evident patients do not care about laboratory values as much as they do about quality-of-life outcomes. 11 However, although criteria such as mortality, hospitalization, and quality of life are important to patients, using them as metrics for payment and public reporting is problematic because of attribution and appropriate case-mix adjustment issues.…”
mentioning
confidence: 99%